Hastanelerde yoğun bakım ünitelerinin hijyenik olarak klimatize edilmesi - Kahraman, Murat (My University, 2006)
Hygen is an important necessity beside the medical treatments in hospitals. Intensivecare units is one of the most requried places in an hospital. Because of the patients in thisunits have weak immunes, even less microorganisms can cause to get infection of the patientsand moreover cause deaths.When it said "hygen" , first it's tought that to wear mask and gloves. But thisextensive subject is beginning with architecture of the hospital and involving HVAC system,especially "air conditioning" system.In this thesis, it's started recent deaths due to infections in intensive care units in ourcountry depending insufficient air conditioning so it's studied all sides of the air conditioningof the intensive care units
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2006
Keywords: Hastanelerde yoğun bakım üniteleri; Enfeksiyon kaynakları; Canlı ve cansız uçucu maddeler